Optimization of GFP Ligand and Development of GFP–Proteolysis Targeting Chimera (GFP–PROTAC) to Study Protein Functions - 김재완 (The Graduate School, Ajou University, 2024)
Proteins are essential macromolecules responsible for a wide array of cellular functions, and malfunctions in their activities can lead to diseases. The use of green fluorescent protein (GFP) as a fusion tag in protein studies enables real–time monitoring of protein functions and localization without altering the protein of interest. GFP is widely used in protein function study due to its broad range of applications, and various GFP-expressing cell lines and animal models have been developed. Methodologies for studying protein functions, such as small molecule, monoclonal antibody, CRISPR, and siRNA are widely used in biological research. However, an approach that satisfies the advantages of each methodology have not been developed. PROTAC (Proteolysis–targeting chimera) is a protein functions regulation technology that utilizes the ubiquitin–proteasome system (UPS) and can overcomes the limitations of existing technologies. In this report, we developed GFP–PROTAC, a PROTAC targeting GFP. GFP–PROTAC has the potential to degrade target proteins labeled with GFP, making it a novel technology that can complement the limitations of existing methodologies for studying protein functions. To develop a GFP ligand for GFP–PROTAC, we confirmed through compound binding modeling and virtual screening that an indole structure binds to GFP. MST assay results showed that compounds 4a, 4n, 4o, 4z, and 4ak had good KD values below 40 µM with GFP. Based on these results, we focused on the 2-(pyrrolidin-1-yl)acetamide–containing compounds. Using this structure, we synthesized various GFP– PROTACs with the thalidomide–based linker. Through the investigation in Colon26–GFP stable cells, compounds 8a, 8b, 8d, 8g, 8i, and 8j demonstrated a reduction in GFP signal by more than 30% as shown by western blot. We identified a GFP-PROTAC that can degrade GFP within cells. This new methodology is expected to have broad applications and can complement the limitations of existing methodologies. _x000D_ [Keywords: Methodology for studying protein functions, ubiquitin–proteasome system (UPS), proteolysis–targeting chimera (PROTAC), green fluorescent protein (GFP), GFP– PROTAC]
학위논문(석사)--분자과학기술학과,2024. 8
Keywords: GFP– PROTAC; green fluorescent protein (GFP); methodology for studying protein functions; proteolysis–targeting chimera (PROTAC); ubiquitin–proteasome system (UPS)